2022
DOI: 10.3390/en15207654
|View full text |Cite
|
Sign up to set email alerts
|

Can MCDA Serve Ex-Post to Indicate ‘Winners and Losers’ in Sustainability Dilemmas? A Case Study of Marine Spatial Planning in Germany

Abstract: Multi-criteria decision analyses (MCDAs) have been developed to support and evaluate decision-making on multi-layered problems. The benefit lies in creating transparency, among other benefits, especially in tackling divergent stakeholder interests. Within the energy transition, area shortage can lead to sustainability trade-offs, calling for the reconciliation of planning processes and satisfactory compromises. While ex ante MCDAs complement planning, the ex post consideration of processes has been less widely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…However, recent advances have indicated that, contrary to the intended sequence, the Area Development Plan went ahead of marine spatial planning [53,68]. Attaining a balance between all interests, including energy and shipping goals, has proven to be challenging and has created some difficulties in negotiating interests [126,127]. Swedish Onshore Wind Energy-Case B Sweden's onshore wind energy planning is supplemented by an informal approach of aligning the national energy target with the lower planning level.…”
Section: German Offshore Wind Energy-case Amentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent advances have indicated that, contrary to the intended sequence, the Area Development Plan went ahead of marine spatial planning [53,68]. Attaining a balance between all interests, including energy and shipping goals, has proven to be challenging and has created some difficulties in negotiating interests [126,127]. Swedish Onshore Wind Energy-Case B Sweden's onshore wind energy planning is supplemented by an informal approach of aligning the national energy target with the lower planning level.…”
Section: German Offshore Wind Energy-case Amentioning
confidence: 99%
“…A holistic and multidisciplinary planning approach thus appears necessary beside positive planning to balance the needs of various stakeholder interests and coordinate efforts through a consensus-driven planning process as far as possible, while such a process is not always easy to achieve [127,159,169]. Stakeholder willingness to discuss and collaborate might also be necessary in achieving energy targets and establishing strategies for 'high-hanging fruit' areas for wind energy.…”
Section: Possible Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…Balancing the effectiveness of formal methods for pushing wind energy development with the need to ensure social acceptability therefore appears crucial. Simply prioritizing wind energy interests in spatial planning without considering the concerns of other stakeholders could lead to a lack of social acceptance, as some countries argue for MSP[125,174,176 for onshore wind energy].…”
mentioning
confidence: 99%
“…. Perceived inequalities caused by encouraged wind energy development may still generate opposition[125,174,176 for onshore wind energy]. Balancing the effectiveness of formal methods for pushing wind energy development with the need to ensure social acceptability therefore appears crucial.…”
mentioning
confidence: 99%